The future of Peacebuilding: climate-related security risks and peacebuilding efforts in Africa. (International Journal of Scientific Research and Management (IJSRM), 2021)
The impacts of climate change are increasingly shaping global peace and security. Effective peacebuilding requires the incorporation of climate sensitivity into peacebuilding efforts so as to anticipate the challenges and respond to them in a timely way. Millions of people around the world are already experiencing its effects, both through slow onset changes such as temperature increase, desertification and sea level rise, and rapid onset events such as floods, heat waves and drought. The effects of climate and environmental changes extend beyond the domain of the environment and into the political and social realm. These effects do not automatically turn into security risks. However, through interactions with existing social, economic and demographic pressures, climate change can multiply risks, exacerbate drivers of insecurity and threaten efforts to prevent conflict and sustain peace. With this in mind, this paper looks into the future of peace building with regards to climate related security risks and peace building efforts in Africa drawing lessons from what is obtaining in some African Countries. Lastly, the paper also gives policy recommendations to African governments on the possible policy reforms that would strengthen institutions to ensure sustainable peace in the face of climate change and its associated risks.